Study on the Standard System Construction of Complex System under the Background of Big Data - Zhu, Xianghua; Jia, Hefeng; Yu, Haiyu; Meng, Kai (2023 7th International Conference on Business and Information Management (ICBIM), 2023)
This paper analyzes the principle of system engineering and the systematic characteristics of the standard system and points out that the standard system is characterized by systematisms and it is suitable to use the system theory to guide the construction of the standard system. The methods of standard system construction are summarized, including the construction method of enterprise standard system determined by GB/T 13016, comprehensive standardization method, model architecture method, etc. Through the research, it is found that these methods can provide theoretical basis for the construction of standard system architecture. Then, based on big data this paper analyzes the development status of China's national standard system, intelligent manufacturing industry standard system and State Grid enterprise standard system from the three levels of country, industry and key enterprises, summarizes the evolution and structural characteristics of the complex system's standard system, summed up interaction relationship between complex system and standard system. On this basis, the construction method of complex system standard system using system engineering method is put forward, including the definition of complex system requirements, the analysis of the status and requirements of the standard system, the design of the standard architecture, the determination of the standard list, the operation and maintenance of the standard system. Finally it takes an standard system as an example to evaluate the applicability of this method.